Serum leptin correlates in fertile and idiopathic infertile Yemeni males: a comparative cross-sectional study - Al-Nawd, Ebraheem A.; Alshowafi, Fairouz K.; Abdullateef, Ahmed A.; Abdulgabbar Noman, Mohammad M.; Albadani, Rashad H.; Al-Mansoub, Majed Ahmed (2022)
This comparative cross-sectional study aimed to evaluate the relationship between serum leptin and testosterone, FSH, LH, PRL and semen quality in fertile and idiopathic infertile Yemeni men. A total of 30 infertile males with unknown causes and 30 age-matched healthy fertile males were enrolled in this study. The body mass index (BMI) and waist circumference (WC) were measured. Semen samples were analyzed according to the WHO manual for semen analysis. Serum samples were tested for hormones. Subjects were then divided into subgroups and compared based on their main seminal findings. The WC, serum leptin, PRL, FSH and LH levels were significantly higher (p < 0.05) in the infertile subjects than in the fertile group. Serum leptin demonstrated a significant positive correlation (p < 0.01) with body weight, BMI and WC in fertile males and a significant negative correlation (p < 0.01) with testosterone in fertile and infertile males. Similarly, a significant positive correlation was found between serum leptin and FSH (p < 0.01) and LH (p < 0.05) levels in the infertile subjects. The findings showed that non-obstructive azoospermic (NOA) patients have significant (p < 0.05) high levels of serum leptin, FSH, and LH. These findings may support the possibility of a direct peripheral negative effect of leptin on testicular steroidogenesis independent of the suggested indirect effect, and it could directly impact spermatogenesis without inhibiting testosterone production. This effect was accompanied by increasing serum PRL levels. Furthermore, serum leptin and gonadotropins were found to be increased in the idiopathic NOA group. The present study provided valuable insights into the fertile and idiopathic infertile Yemeni males and could establish an important foundation for future andrological-related studies such as investigating the relationship between leptin and other hormones; and infertility-related genetic and epigenetic factors.